Evolutionary clustering annotation of ortho-paralogous gene in a multi species using Venn diagram visualization - Nair B J, Bipin; M S, Sarath (International Journal of Engineering and Technology, 2018)
The evolutionary analysis of the genome of the immediate cluster is an important part of comparative genomics research. Identifying the overlap between immediate homologous clusters allows us to elucidate the function and evolution of proteins between species. Here, we report a network platform called Ortho-paralogous Venn-diagram representation that can be used to compare and visualize a wide range of ortho-paralogous clustering of genomes. In our work Ortho-paralogous Venn-diagram results show a functional summary of interactive Venn diagrams, summary counts, and interspecies shared cluster separations and intersections. Ortho-paralogous Venn-diagram also uses a variety of sequence analysis tools to gain an in-depth understanding of the cluster. In addition, Ortho-paralogous Venn identifies direct homologous clusters of single copy genes and allows custom search of specific gene clusters. It enables us in wide analysis of the genes and protein by comparing the genes using Venn diagram .Here the user can upload our own gene sequences into the application ,using three clustering approach to check the best clustering approches like SOM,K-means and advanced clustering after that we are using the Venn diagram repersentator to evolutionary cluster the genes having similar functionality and structural similarity from the uploaded data.Here we are using a venn diagram representation as an application which used to cluster the orthologous and paralogous gene on basics of their evolution and functional aspects.it enables us in wide analysis of the genes and protein bycomparing the genes using venn diagram representation.here the user can upload our own gene sequences into the application where the venn diagram representatorclusters.the genes having similar functionality and structural similarity from the uploaded data.